Crowd social pressure in the Brazilian soccer league: testing home advantage and referees` bias during the COVID-19 pandemic - Couto, B. P.; Sayers, M. G. (International Journal of Sport and Exercise Psychology, 2022)
Although the home advantage is a well-documented phenomenon in soccer, the effect of the home crowd social pressure on teams and referees` performance remains unclear. The COVID-19 pandemic brought a unique opportunity to test the real effect of the crowd. The aim of the present study was to analyse the home advantage and referee bias in the Brazilian soccer league, comparing whole seasons played with and without spectators. Match data from 2003 to 2020 were compared. The points earned, victories, and goals scored were used to analyse teams` performance. Referee bias was investigated by the extra time, yellow and red cards awarded. Difference of points and victories, between home and away teams, during the 2020 season was similar to most of the previous seasons and showed a decreasing tendency throughout the seasons. When comparing the 2019 and 2020 seasons, the home advantage, measured by the relative number of points won at home, was present in games played with (60.9 ± 7.7%) and without (60.4 ± 6.3%) spectators. Home teams showed higher number of victories, total points, and goals scored (p < 0.001 each). Away teams were awarded with a higher number of yellow cards (p = 0.008), but this number was smaller during the pandemic (p = 0.049). Games played with spectators received less minutes of extra time in the second half when away teams were losing by a difference of one goal (p = 0.012). In conclusion, the absence of spectators in the Brazilian soccer league during the COVID-19 pandemic did not reduce the home advantage but affected the referee bias.